1Q84 - Murakami, Haruki, 1949- (Vintage International, 2013)
An ode to George Orwell's "1984" told in alternating male and female voices relates the stories of Aomame, an assassin for a secret organization who discovers that she has been transported to an alternate reality, and Tengo, a mathematics lecturer and novice writer.